Drivers of phylogenetic structure in Amazon freshwater fish assemblages. (24th December 2021) - Salgueiro, Laís; Cassemiro, Fernanda A. S.; Albert, James S.; Frederico, Renata G.; Hidalgo, Max; Hugueny, Bernard; Jézéquel, Céline; Ortega, Hernan; Tedesco, Pablo A.; Torrente‐Vilara, Gislene; Zuanon, Jansen; Oberdorff, Thierry; et al.
Abstract: Aim: Phylogenetic relatedness among species can provide useful information on the diversification history and past dispersal events that may have shaped contemporary assemblages. Here, using of the most comprehensive fish occurrence database currently available and a global molecular phylogeny of ray‐finned fishes, we evaluate the respective roles of historical and contemporary processes in generating and maintaining fish assemblage phylodiversity patterns among 97 sub‐drainages covering the Amazon River basin. Location: Amazon River basin. Taxon: Freshwater fishes. Methods: Using a large comprehensive database of freshwater fish species distributions, and a global molecular phylogeny of ray‐finned (actinopterygian) fishes, we estimated historical and contemporary environmental effects on sub‐drainage fish phylodiversity patterns using three phylogenetic metrics standardized for richness effect: Phylogenetic Diversity (ses.PD), Mean pairwise Phylogenetic Distance between species capturing patterns at older evolutionary timescales (ses.MPD), and Mean Nearest Taxon Distance capturing patterns at younger evolutionary timescales (ses.MNTD). Results: We found significant effects of elevation gradients, contemporary climate, and water types on assemblage phylodiversity patterns. Furthermore, we found significant relationships among the three phylogenetic metrics used, and between these metrics and the distance of sub‐drainages to the Amazon River mouth, representing the Amazon basin West‐East longitudinal gradient. Main conclusions: Phylogenetic diversity showed a highly non‐random spatial distribution across the Amazon basin. Beyond significant regional effects of several contemporary and historical drivers, there was a significant West‐East decline in sub‐drainage assemblages phylogenetic clustering, along with an increase in phylogenetic diversity. These latter patterns suggest deeper evolutionary divergences among taxa located to the East, and more recent radiations in the Western sub‐drainages. Based on these findings and given that assemblages are, on average more species‐rich in sub‐basins of the Western part of the basin than in their Eastern relatives, we conclude that Western Amazon can be seen as an evolutionary "cradle" of biodiversity for freshwater fishes.